The Mediating Role of Operational and Environmental Performance in the Relationship between Green Supply Chain Management and Financial Performance - Chairit Thongrawd; Pipat Pichetsiraprapa; Narintorn Somthong; Kittiampol Sudprasert (International Journal of Supply Chain Management, 2019)
The study is carried out with an objective to explore the impact of green supply chain management on different performance measures such as environmental performance, operational performance and financial performance. In addition to that, the mediating role of operational performance and the environmental performance in the relationship between green supply chain management and the financial performance is also examined. The study has broached a new perspective, that is external and internal GSCM practices are essential in the SC strategies, as these practices facilitate firms in enhancing market share and profits only when jointly implemented, by improving ecological efficiency and minimizing environmental risks. Therefore, the objective of this paper is to examine the interrelationships between GSCM approaches, performance, and environmental drivers. SEM-PLS is used to achieve the research objective of the current study. The study which is on Indonesian is in author knowledge is among few pioneering studies exploring the interaction of green supply chain management as determinant of firm performance measures. This study will be helpful for policymakers and researchers in examining the link between supply chain management on different performance measures such as environmental performance, operational performance and financial performance for Indonesian settings.